Residents Perception and Attitude of Tourism Development: A Case Study of Patan Durbar Square the World Heritage Site - Koirala, Narayan (Interdisciplinary Journal of Management and Social Sciences, 2020)
Tourism is growing rapidly and is one of the most important industry in many developing countries. The tourism sector has become major factor of importance in the world GDP because of its rapid growth and development. It is a power force of change in the economy. So, development of tourism influences the development of other sector such as agriculture, food processing, handicraft etc. which can contribute to the well-being of the entire community. Tourism development is strongly related to local communities. Local people are a key element that helps in the development of tourism. They are the important component that influence the future development of tourism destination. The development of certain area or place is impossible without the help of people living in that area. Therefore, the involvement and participation of local people is very important for the development of any sector. Tourism development is one of the important components for the economic growth of the country. In this respect, the perception and attitude of local people plays the most important role. So, the present study provides an idea about the tourism development by the local people perception and explore the need of the tourist by identifying their problems and study the involvement of local people for its development. Based on the survey, the analysis revealed that the facilities like internet, parking facilities, information center, sanitation, safety and security, good food, pure drinking water are the most needed facilities. This study also analyzed that government sector plays a significant role and is required in the development of tourism through infrastructure and hospitality. The infrastructure like road and transport, electricity, water and hospitality like communication, accommodation, and food and beverages. This study also explains that the involvement of local people through various activities like trade and business, maintaining good environment, hospitality, cultural program. The major problems like lack of sanitation, information center, shops in every place in unmanaged way, lack of infrastructure was also revealed by this study.